JAVASCRIPT FROM FRONTEND TO BACKEND learn full stack javascript using the MEVN stack with quick and easy steps - Sarrion, Eric (PACKT PUBLISHING LIMITED, 2022)
Delve into the world of web development with Vue.js, Node.js, and MongoDB by exploring essential JavaScript concepts on the client side and the server side Key Features Get up and running with JavaScript, the most popular web development language in the world Cut through the complexity and focus on the simple aspects of web development Build a simple web application using Vue.js, Node.js, and MongoDB Book Description JavaScript, the most widely used programming language in the world, has numerous libraries and modules and a dizzying array of need-to-know topics. Picking a starting point can be difficult. Enter JavaScript from Frontend to Backend. This concise, practical guide will get you up to speed in next to no time. This book begins with the basics of variables and objects in JavaScript and then moves quickly on to building components on the client-side with Vue.js and a simple list management application. After that, the focus shifts to the server-side and Node.js, where you'll examine the MVC model and explore the Express module. Once you've got to grips with the server-side and the client-side, the only thing that remains is the database. You'll discover MongoDB and the Mongoose module. In the final chapter of this fast-paced guide, you'll combine all these pieces to integrate a Vue.js application into a Node.js server, using Express to structure the server code and MongoDB to store the information. By the end of this book, you will have the skills and confidence to successfully implement JavaScript concepts in your own projects and begin your career as a JavaScript developer. What you will learn Trigger deferred processing with JavaScript Implement Express and MongoDB with Node.js Build components with Vue.js Understand how to create and use modules with Node.js Familiarize yourself with npm Build a client-side application entirely with JavaScript Dive into full stack development with Vue.js, Node.js, and MongoDB Who this book is for This book is for JavaScript developers looking to strengthen their core JavaScript concepts and implement them in building full stack apps. Prior knowledge of HTML and CSS is a must.